Pengukuran Laju Sedimentasi dan Kualitas Air Kolam Patin Menggunakan Sedimen Trap di Kelurahan Rumbai Bukit - Saberina Hasibuan; Novreta Ersyi Darfia; Rahmat Iman Mainil; Naufal Arif Budiman; Ayu Mita Jami Yanti; Aura Zulvani S; M. Ibnu Sina Zikri; Jacklin Mendy; Saipul Anwar Nasution; Suci Rahmadhani Irawan; Sofia Zuhrah; Nabila Putri Maharani; Erlangga Dwi Atha (PRIMA: Journal of Community Empowering and Services, 2025)
Measurement of Sedimentation Rate and Water Quality in Catfish Ponds Using Sediment Trap in Rumbai Bukit Subdistrict. Rumbai Bukit in Pekanbaru City, Riau Province, has aquaculture potential supported by the fish farming group mina usaha, which cultivates catfish (Pangasianodon hypophthalmus) in earthen ponds. The aim of this community service activity was to monitor the quality of catfish ponds using sediment traps, carried out in collaboration with Student Community Service from the University of Riau over a period of 40 days. This activity involved local fish farmers in Rumbai Bukit. Ten students provided assistance to improve pond productivity by monitoring pondquality through measurements of sedimentation rate, temperature, Total Dissolved Solids (TDS), and pH. Following the measurements, training was conducted and followed by continuous monitoring of water quality and fish growth. The analysis of water quality in relation to fish growth resulted in a graph showing the relationship between feed application and physical water parameters. The sedimentation rate in pond one was relatively high, averaging 71.85 ml/L, compared to 16 ml/L in pond two. The temperature in pond one ranged from 32°C to 35°C, while in pond two it ranged from 31°C to 34°C. TDS levels in pond one were relatively high, ranging from 112 to 194 ppm, compared to 9 to 24 ppm in pond two. The pH in pond one ranged from 6.9 to 7.5, while in pond two it ranged from 6.3 to 7.1. This community service activity was well received, with around 70% of fish farmers enthusiastically participating. The use of sediment traps was effective in monitoring sediment accumulation in catfish ponds. Ponds with poor management showed thicker sediment layers and a decline in water quality. Regular monitoring and efficient feed management are recommended to maintain optimal water quality and fish health. This activity has made a tangible contribution by increasing fish farmers' awareness and capacity regarding the importance of regular water quality monitoring, and by encouraging the adoption of more sustainable aquaculture practices to support local food security and the environmental sustainability of aquaculture in the Rumbai Bukit area.